Macrophage Polarization, Metabolic Reprogramming, and Inflammatory Effects in Ischemic Heart Disease - Sun, Xiaoqian; Li, Yanqin; Deng, Qiong; Hu, Yueyao; Dong, Jianteng; Wang, Wei; Wang, Yong; Li, Chun (Frontiers in Immunology, 2022)
Macrophages are highly plastic cells, and the polarization-activating actions that represent their functional focus are closely related to metabolic reprogramming. The metabolic reprogramming of macrophages manifests itself as a bias towards energy utilization, transforming their inflammatory phenotype by changing the way they use energy. Metabolic reprogramming effects crosstalk with the biological processes of inflammatory action and are key to the inflammatory function of macrophages. In ischemic heart disease, phenotypic polarization and metabolic shifts in circulating recruitment and tissue-resident macrophages can influence the balance of inflammatory effects in the heart and determine disease regression and prognosis. In this review, we present the intrinsic link between macrophage polarization and metabolic reprogramming, discussing the factors that regulate macrophages in the inflammatory effects of ischemic heart disease. To establish reliable regulatory pathways that will allow us to better target the macrophage metabolic reprogramming process and improve the symptoms of ischemic heart disease.